A Parachlorella kessleri (Trebouxiophyceae, Chlorophyta) strain tolerant to high concentration of calcium chloride. (29th October 2021) - Liu, Xudong; Zhao, Jinli; Feng, Jia; Lv, Junping; Liu, Qi; Nan, Fangru; Xie, Tao; Xie, Shulian
Abstract: Members of coccoid green algae have been documented in various extreme environments. In this article, a unicellular green alga was found to slowly grow in high concentration (3.6 g/L) and pure calcium chloride solution in the laboratory. It was successfully cultured and a taxonomic study combined approaches of morphological and molecular methods was conducted to determine its classification attribution, which was followed by a preliminary physiology research to explore its unique tolerance characteristics against calcium chloride stress. The strain was identified as Parachlorella kessleri by very similar morphology and the same phylogenetic position. The morphological differences among the three species in genus Parachlorella were then discussed and the characteristic traits of absent or thin mucilaginous envelop and mantel‐shaped chloroplast for P. kessleri were supported. In addition, the almost strictly spherical shape of adult cells could further distinguish the P. kessleri from the other two species. The tolerant characteristics to CaCl2  stress for this strain were confirmed and the limit concentration was revealed as between 2000 and 4000 times than the standard BG11 culture concentration. Therefore, this P. kessleri strain is expected to be a good material to explore the mechanism of resistance to calcium ions stress for eukaryotic microbiology.